2012
DOI: 10.1007/s11248-012-9668-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a murine germ cell-specific knockout of Connexin 43 on Connexin expression in testis and fertility

Abstract: Connexin 43 (Cx 43)--expressed by germ cells (GC), Sertoli cells (SC) and Leydig cells--is one of at least eleven Cx in the murine testis. A general knockout (KO) of Cx 43 in mice results in perinatal death and a SC-specific KO of Cx 43 (SCCx43KO) causes infertility of male mice by preventing the initiation of spermatogenesis. To further elucidate the role of Cx 43 in the testis, a new mouse model with a GC-specific KO of Cx 43 (GCCx43KO) was created by using the Cre/loxP recombination system. A transgenic mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Moreover, the gap junctions, including connexin‐43, promote cross talk between various junction types to keep BTB homeostasis, which play vital functions in the development and maturation of spermatozoa . Connexin‐43 knockout mice can result in perinatal death, and SC‐specific knockout of Connexin‐43 can cause infertility by restraining the initiation of spermatogenesis in male mice . The results indicated that the damage of testicular BTB integrality could cause the male reproductive toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the gap junctions, including connexin‐43, promote cross talk between various junction types to keep BTB homeostasis, which play vital functions in the development and maturation of spermatozoa . Connexin‐43 knockout mice can result in perinatal death, and SC‐specific knockout of Connexin‐43 can cause infertility by restraining the initiation of spermatogenesis in male mice . The results indicated that the damage of testicular BTB integrality could cause the male reproductive toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Connexin-43 knockout mice can result in perinatal death, and SC-specific knockout of Connexin-43 can cause infertility by restraining the initiation of spermatogenesis in male mice. 30 The results indicated that the damage of testicular BTB integrality could cause the male reproductive toxicity.…”
Section: Pm 25 Activated P38 Mapk Signaling In Testes Of Ratsmentioning
confidence: 99%
“…Second, the population of Sertoli cells is not grossly affected in adjudin‐treated rats (4), whereas Sertoli cells remains mitotically active in Sertoli cell‐specific Cx43 KO mice (36), and aggregates of undifferentiated Sertoli cells are being shed from the epithelium and found in tubule lumen in these mice (12) but not in adjudin‐treated rat testes (4). In this context, it is of interest to note that in germ cell‐specific Cx43 KO mice, these mice remain fertile without the noted phenotypes seen in the Sertoli cell‐specific Cx43 KO mice (37). The findings using germ cell‐specific Cx43 KO mice support the notion that the deleted Cx43 function in germ cells can be superseded by other connexins, but not when Cx43 was deleted in Sertoli cells, because the testis is known to express at least 10 different connexins in rodents, such as Cx33 and Cx26 (10, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Cx45, a second member of the Cx family, was subsequently detected in interstitial cells (and within the seminiferous epithelium) of the testis via β-galactosidase IHC, although the cells expressing this marker were not actually determined (Krueger et al 2000). Further studies showed the expression of Gjc1/Cx45 in rodent testicular tissue, namely in whole testis homogenates (Giese et al 2012;Guenther et al 2013), in cells of the seminiferous epithelium (Risley 2000), and in cells contributing to the blood vessels (Krueger et al 2000). In the study of Li et al (2013), mRNA of isolated adult murine LC was systematically screened for transcripts of 19 different Cx.…”
Section: Discussionmentioning
confidence: 99%